2006
DOI: 10.1203/01.pdr.0000242364.78002.71
|View full text |Cite
|
Sign up to set email alerts
|

Altered Placental and Fetal Expression of IGFs and IGF-Binding Proteins Associated With Intrauterine Growth Restriction in Fetal Sheep During Early and Mid-Pregnancy

Abstract: ABSTRACT:The insulin-like growth factors (IGFs) are postulated to be altered in association with the development of intrauterine growth restriction (IUGR). The present studies examined placental and fetal hepatic mRNA concentration of components of the IGF system at two time points (55 and 90 d gestational age, dGA; Term 147 dGA) in a hyperthermia (HT)-induced sheep model of placental insufficiency-IUGR. Maternal plasma insulin and IGF-I were constant at 55 and 90 dGA and were unaffected by treatment. Umbilica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 42 publications
1
47
1
Order By: Relevance
“…In the caruncle, IGFBP-2 was unaffected by maternal GH treatment. Previously, it was believed that IGFBP-1 was not expressed beyond 21 dGA (Wathes et al 1998, de Vrijer et al 2006; however, here we could detect changes in IGFBP-1 by treatment at 55 dGA. We do not discount the previous results, as our detection of IGFBP-1 is most likely due to the increased sensitivity of qPCR versus hybridization technologies in detecting transcripts.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In the caruncle, IGFBP-2 was unaffected by maternal GH treatment. Previously, it was believed that IGFBP-1 was not expressed beyond 21 dGA (Wathes et al 1998, de Vrijer et al 2006; however, here we could detect changes in IGFBP-1 by treatment at 55 dGA. We do not discount the previous results, as our detection of IGFBP-1 is most likely due to the increased sensitivity of qPCR versus hybridization technologies in detecting transcripts.…”
Section: Discussioncontrasting
confidence: 76%
“…5 8C to 95 8C. For the qPCR analysis, cDNA for ovine IGF-I, IGF-II, and IGFbinding proteins (BP) 1, 2, 3, and 4 (de Vrijer et al 2006) and RPS15 (Rozance et al 2007) were used as standard templates. The standard curve template concentrations spanned 100 to 1!10 K5 pg/ml at tenfold increments.…”
Section: Northern Hybridization Analysismentioning
confidence: 99%
“…Many studies have reported increased placental expression of IGF-I and IGF-II in IUGR pregnancies [33, 34] and, similarly, elevated levels of placental IGF-I and-II mRNA have been observed in a sheep model of IUGR [35]. These findings are somewhat surprising as, like in cord blood, a decrease in placental IGF levels might have been anticipated.…”
Section: The Igf Axis In the Placentamentioning
confidence: 99%
“…Elevated expression levels of paternally imprinted gene IGF2 in the placenta have been correlated with foetal growth restriction in humans (Street et al 2006) and sheep (de Vrijer et al 2006) and with early embryonic lethality of somatic cell nuclear transferderived cows (Oishi et al 2006). Since low birthweight in humans may be an important risk factor for the development of neurological disorders and adult-onset diseases such as coronary heart disease, stroke, hypertension, type II diabetes and osteoporosis, ovarian stimulation could even have adverse effects in adult life (Fleming et al 2004).…”
Section: Perinatal Outcomesmentioning
confidence: 99%